2005
DOI: 10.1080/10245330500065797
|View full text |Cite
|
Sign up to set email alerts
|

Soluble VEGF/sFLt1 ratio is an independent predictor of AML patient out come

Abstract: Angiogenesis is the formation of new blood vessels and is controlled by a balance between positive and negative angiogenic regulatory factors. Soluble vascular endothelial growth factor receptors 1,2 (Flt-1, KDR) are the negative counterpoint to the vascular endothelial growth factor (VEGF) signaling pathway, which has been characterized as one of the most important endothelial regulator in human angiogenesis. In the present work, we tested the differential prognostic relevance of soluble vascular endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 12 publications
0
47
0
2
Order By: Relevance
“…VEGF-A/ sVEGFR-1 index was assessed in patients with pancreatic cancer and acute myeloid leukemia with regard to the severity of the disease and prognosis (Aref et al, 2005;Chang et al, 2008). This parameter could be used in practice to assess the degree of severity of PAD, which is the subject of the current research (Rość et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A/ sVEGFR-1 index was assessed in patients with pancreatic cancer and acute myeloid leukemia with regard to the severity of the disease and prognosis (Aref et al, 2005;Chang et al, 2008). This parameter could be used in practice to assess the degree of severity of PAD, which is the subject of the current research (Rość et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…www.aacrjournals.org in a variety of cancers, including breast and colorectal carcinomas (35), melanoma (20), and a number of blood cell-related malignancies (21)(22)(23)(24); however, the utility of this protein as a potential biomarker remains unclear. To further investigate the relationship between sVEGFR-2 levels and tumor burden, we examined plasma obtained from various preclinical mouse tumor models that included spontaneous and implanted tumors, as well as localized and metastatic disease.…”
Section: Vegf Modulates Svegfr-2mentioning
confidence: 99%
“…We first reported the existence of this 160-kDa truncated protein, which could be detected in both mouse and human plasma (19). Recent clinical studies have involved investigations into its potential as a surrogate biomarker for tumor progression or survival in melanoma (20), myelodysplastic syndromes (21), as well as in various leukemias (22)(23)(24). However, no clear pattern has yet emerged to indicate the utility of monitoring circulating sVEGFR-2 in the clinical setting, how it relates to tumor growth, and the underlying mechanisms governing observed changes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the few known physiological roles of sVEGFR1 is its antiangiogenic participation in the maintenance of corneal avascularity (2). In contrast, the pathological involvement of sVEGFR1 is being discovered in a growing list of VEGF-dependent disease conditions, from preeclampsia (1,25,39) to cancers (3,4,8,23) to liver cirrhosis (18), sepsis (35), and possibly peripheral arterial disease (16).…”
mentioning
confidence: 99%
“…The second and third extracellular Ig-like domains of the VEGFR1 protein are generally believed to confer its ligand-binding capacity (5,12), while the fourth Ig-like domain was found responsible for receptor dimerization (5,7). Several in vitro and in vivo studies have suggested that gene delivery of solely the first three Ig-like domains of VEGFR1 (ECD [1][2][3] ) was effective in inhibiting VEGF-mediated corporal tissue vasoreactivity in rabbits (41), as well as in inhibiting human umbilical vein endothelial cell (HUVEC) proliferation and tumor angiogenesis in mice (24,42,44). This may suggest that VEGF binding through ECD [1][2][3] alone is sufficient to simulate sVEGFR1's antiangiogenic effects.…”
mentioning
confidence: 99%